Study on the Revolt of 1857 Reasons and Impact: The Rebellion that Shaped India's Path to Freedom (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Therevolt of 1857 marked a turning point in the history of India. It was theheralding of a new age. It crowned the dawn of India’s independence from thefetters of foreign rule that had bound her. It was, in fact, the first essay inIndia’s advent to freedom. It laid the foundation of Indian nationalism. Itacted as a great inspiration to our countrymen, who felt inspired by theexample set by the rebels who had died fighting the British despite the heavyodds against them.